2011
DOI: 10.1111/j.1574-6976.2010.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin: a multidomain host adhesin targeted by bacterial fibronectin-binding proteins

Abstract: Fibronectin, a large and essential multidomain glycoprotein, with multiple adhesive properties, functioning as a key link between cells and their extracellular matrices, is now recognized to be the target for a large number of bacterial proteins, which are generally considered to function as bacterial adhesins. In the last decade, an avalanche of bacterial fibronectin-binding proteins (FnBPs) has been identified, and the bioinformatics, structural biology, biological function and role in the virulence of a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
290
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(298 citation statements)
references
References 461 publications
(675 reference statements)
4
290
0
4
Order By: Relevance
“…FBD5 (IPR004237) is certainly the domain having attracted the most interest (Henderson et al, 2011). It is exclusively found in the phylum Firmicutes, essentially the genera Staphylococcus and Streptococcus.…”
Section: Fibronectin and Fibronectin-binding Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…FBD5 (IPR004237) is certainly the domain having attracted the most interest (Henderson et al, 2011). It is exclusively found in the phylum Firmicutes, essentially the genera Staphylococcus and Streptococcus.…”
Section: Fibronectin and Fibronectin-binding Proteinsmentioning
confidence: 99%
“…Interestingly, the ability to bind soluble fibronectin would vary from one fibronectinbinding protein (FnBP) to another; e.g. PavA cannot but Fbp54 can bind the soluble form (Henderson et al, 2011). With 1160 species, FBD3 is the most largely distributed FBD in bacteria.…”
Section: Fibronectin and Fibronectin-binding Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the low number of recognized bacterial FNIII domains at that time, and phylogenetic analysis placing them separate from the eukaryotic domains, it was suggested that prokaryotes had acquired FNIII domains from eukaryotes [7]. All initially identified prokaryotic FNIII domains were associated with carbohydrate acting enzymes, but more recently these domains have also been identified in fibronectin binding proteins and multiple other prokaryotic protein types [8][9][10]. Our database searches showed that about 33% of all FNIII containing proteins included in SMART database (15125) [10] are from bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 In addition, a number of studies suggested an active role of FN adsorption in cellular uptake of nonviral nanocarriers (for review, see Adler et al 22 A large amount of bacterial FN-binding protein has been identified so far; among them is BBK32, a 47 kDa surfaceexposed lipoprotein and FN-binding adhesin of Borrelia burgdorferi (B. burgdorferi). 23,24 BBK32 contains multiple FN-binding motifs located to an extended intrinsically disordered segment. 25 It was shown that the region of BBK32 comprising amino acids 147 -205 binds to the N-terminal FNI and FNIII modules, but residues 120 -147 of BBK32 protein are considered similar to the FN-binding region of SfbI protein from S. pyogenes that had been shown to bind to the GBD of FN.…”
mentioning
confidence: 99%